The Influence of Managerial Ownership on Company Value in Manufacturing Companies - Kurniawati, Desi; Febriyanto, Muhammad Ikhsan; Erliana, Erliana; Yulyanah, Yulyanah (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2025)
The purpose of this study is to determine the Effect of Managerial Ownership on Company Value. This study uses a descriptive quantitative approach with data collection techniques using secondary data. The study population includes companies listed on the Indonesia Stock Exchange in 2020-2023. Sampling in this study used the purposive sampling method, so that a sample of 248 research samples was obtained. The data used in this study uses secondary data obtained from the annual report of mining companies. The data analysis method used is multiple linear regression analysis using the Eviews 10 program. The results of the study Managerial Ownership has a positive effect on Company Value.